Legal Standing Pemohon dalam Perkara Pembubaran Partai Politik Berdasarkan Prinsip Negara Demokrasi - Rahmah Nurlaily; Moh Ali Wafa; Irfan khairul Umam (JOURNAL of LEGAL RESEARCH, 2020)
This research is to know how the provisions regarding the legal standing dissolution of political parties in the country of democracy, namely Indonesia and Germany, and know the legal position of the applicant in the case of dissolution of political parties in Indonesia in accordance with the principles of democracy, this is based on studies with the German state. This research uses the type of normative research, in this research method of data collection is done by Library Research technique, by studying the literature, rules of invite-invitations, books, official documents, and writings of scholars related to this thesis. The Data has been compiled and analyzed using a juridical normative method or qualitative method, which is a study that specialized in the study based on the legal theories that are then associated with legislation.The approach used in this research is a statutory approach as well as an analytical approach. The results of this research showed a comparison of legal standing applicants for the dissolution of political parties in Indonesia with Germany, where Indonesia has similarities with the German state that both have a multi-party system as well as the authority to dissolution its political party owned by the Constitutional Court, but in the application of a legal standing applicant dissolution of a different political party, which German , the implementation is already based on the principle of democracy, unlike Indonesia which legal standing applicants only government only, of course this is not based on the principle of democracy state when mirrored to the German state. That there should be other parties who become applicants in the case of the dissolution of political parties in Indonesia, namely the DPR and DPD, it reflects the life of a democratic country and the oversight of the political parties and governments who become parties in the application of the dissolution of the political party, for that it is necessary to study the authority of the applicant in the dissolution of political parties in